A comparative study of ultrasonography versus magnetic resonance imaging in the diagnosis of abnormally adherent low lying placenta - Ashraf, Mohd.; Noor, Humera; Afzal, Asima; Rasool, Irfana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: When placenta is implanted partially or completely over the lower uterine segment it is called as placenta previa. Abnormalities associated with placenta previa include placenta accreta, placenta increta and placenta percreta. Prenatal diagnosis of placental abnormalities was earlier difficult but now a day’s placentography is done using gray scale ultrasonography and more recently magnetic resonance imaging with or without gadolinium has been explored as a modality to optimize diagnostic accuracy. The objective of this study was to compare the effectiveness of ultrasonography and magnetic resonance imaging in diagnosis of placental abnormalities in patients having low lying placenta. The Design of this study was a prospective study conducted in a tertiary care hospital. Methods: This study was conducted on 100 admitted pregnant females with gestational age 30-37 weeks with low lying placenta (previa), haemodynamically stable and having past history of uterine surgeries like caesarean delivery, dilatation and curettage and myomectomy. After confirming gestational age and low lying placenta on Ultrasonography, the detailed USG study was done. All the patients in the study group underwent MRI which was performed without contrast. Results: Among 100 cases, most of the patients were in the age group of 26-30 (52%), the least common age group was 20-25 (4%). Out of 100 studied cases 29 were gravid two with 20.6% associated PAD, 34 were Gravida three with 29.4 % PAD, 21 were gravid four with 23.8% PAD. Among 100 studied cases, dilatation and curettage was absent in 37 cases, out of that 22 had undergone one caesarean section, 13 had undergone two caesarean section and 2 cases had undergone three caesarean section. USG showing sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 53.3, 90.0, 69.6 and 81.8 % respectively. X2=22.266 and p=0.00. MRI showing sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 73.3, 91.4, 78.6 and 8.89 % respectively.X2=43.689 and p=0.001. Conclusions: Prenatal diagnosis is a key factor in optimizing the counseling, treatment and outcome of patients with placental adhesive disorder. Any women with placenta previa and previous uterine surgery should undergo careful imaging to assess the presence of placental adhesive disorder. Magnetic resonance imaging appears better diagnostic aid as compared to ultrasonography in diagnosing placental adhesive disorder.